Desinformação na era digital: um estudo sobre os hábitos de consumo de notícias por adolescentes de São Paulo - Ribeiro, Ana Carolina Vieira (2023)
In a context of intense digital mediation in all spheres of life, social media on the Internet transforms the information landscape, impacting on the production, dissemination and consumption of news. In this research we investigate how this complex context affects and is affected by contemporary youth. We start from the presupposition that young people, who grew up immersed in a society frequently permeated by the digital, acquire a significant part of their perception of the world through social media even if informally. The applied methodology consists of bibliographic research, followed by quantitative research with 56 adolescents: 32 from public schools and 24 from private schools. Of the 56 respondents, 30 are girls, 21 boys and 5 young people, who do not identify exclusively with the gender binary. The reason for choosing the questionnaire as a data collection instrument was motivated by the possibility of reaching more respondents and providing data from the interviewee’s point of view (GIL, 1995). As a theoretical basis, we rely on the works of David Buckingham, Eugênio Bucci, Carlos A. Scolari, Lucia Santaella, all of whom study digital technologies and their impact on culture, the flow of information and the phenomenon of misinformation